Treatment of teeth in the esthetic zone in a patient with amelogenesis imperfecta using composite veneers and the clear matrix technique: A case report - Bogosavljević Aleksandar; Mišina Vanja; Jordačević Jovana; Abazović Milka; Dukić Smiljka; Ristić Ljubiša; Daković Dragana (Vojnosanitetski Pregled)
Introduction. Restorative dental treatment of patients with a generalized form of amelogenesis imperfecta (AI) remains a challenge even today. The treatment approach is multidisciplinary and includes action of several dental disciplines such as restorative, orthodontic, and prosthetic dental specialties. Case report. A 18-year-old female patent was referred to the Department of Restorative Dentistry and Periodontology at the Military Medical Academy of Belgrade, Serbia. She was diagnosed with AI and formerly had been treated for a long period of time at the Department of Pediatric Dentistry and Orthodontics. Her primary concern upon arrival was discomfort and concern for the esthetic appearance of the anterior teeth. The treatment was done with the modified clear matrix technique used in composite veneer restoration of teeth in the esthetic zone. Conclusion. Because fixed prosthetic restoration with crowns, is the final treatment of AI patients it involves severe tooth structure loss. The clear matrix method which was done in this case allowed for greater comfort, functionality, simplicity, speed, greater economic efficiency and tooth structure preservation.